2018
DOI: 10.1111/jcal.12318
|View full text |Cite
|
Sign up to set email alerts
|

Process assessment in dynamic testing using electronic tangibles

Abstract: Task solving processes and changes in these processes have long been expected to provide valuable information about children's performance in school. This article used electronic tangibles (concrete materials that can be physically manipulated) and a dynamic testing format (pretest, training, and posttest) to investigate children's task solving processes and changes in these processes as a result of training. We also evaluated the value of process information for the prediction of school results. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 60 publications
2
21
0
Order By: Relevance
“…One of the major contributions of computerised approaches is that these can utilise tangible materials that can lead to the capture of a mass of data (e.g. response latencies) that are not easily obtainable, or recorded, as part of the complex interpersonal dynamics of human-human testing (Resing and Elliott 2011;Resing, Touw, et al 2017;Veerbeek et al 2017). It will be interesting to see whether the development of what is likely to be an increasingly rich area of research will succeed in resolving the fundamental questions raised in the 2003 review, and which are further addressed below.…”
mentioning
confidence: 99%
“…One of the major contributions of computerised approaches is that these can utilise tangible materials that can lead to the capture of a mass of data (e.g. response latencies) that are not easily obtainable, or recorded, as part of the complex interpersonal dynamics of human-human testing (Resing and Elliott 2011;Resing, Touw, et al 2017;Veerbeek et al 2017). It will be interesting to see whether the development of what is likely to be an increasingly rich area of research will succeed in resolving the fundamental questions raised in the 2003 review, and which are further addressed below.…”
mentioning
confidence: 99%
“…The merits of using a robot as a support assistant in dynamic testing seem obvious. Earlier studies (Henning, Verhaegh, & Resing, 2010;Resing et al, 2017;Veerbeek, Vogelaar, Verhaegh, & Resing, 2019) have already shown the positive aspects of the use of an electronic console for dynamic testing. The current study replicates this but within a different task domain, and goes one step further.…”
Section: Discussionmentioning
confidence: 97%
“…First, we aimed to evaluate the effects of the computerized graduated prompts training on both the performance and solving behavior of children on the computerized dynamic test of analogical reasoning. It was expected that children who received training would show more progression from pretest to posttest in terms of analogical reasoning (1) task-solving accuracy (number of items answered correctly), and (2) accuracy on transformations (transformations answered correctly), but this change was not expected to be reflected in (3) the solving processes as reflected by the process indicators obtained from the log data, as found in prior research (Veerbeek et al, 2019).…”
Section: Study Aimsmentioning
confidence: 88%